Management of the design and construction process of a thermal power plant under conditions of permafrost instability. Issue 1 (January 2021) - Didenko, N I; Skripnuk, D F; Bobodzhanova, L K; Hazov, V K
Abstract: The key issues of the process of the design and construction of a thermal power plant and the life cycle management of a thermal power plant under conditions of permafrost instability are considered. The article aims to develop information, mathematical and software support for the design and construction process supervising and testing of construction objects of a thermal power plant and life cycle management of a thermal power plant under conditions of permafrost instability. The following tasks arising in the process of achieving the given goal are presented: to study the characteristics of the constructed thermal power plant; to present the design and construction process of a thermal power plant in the form of an alternative graph; to identify alternatives and risks in the life cycle management system; to develop an investment project for a thermal power plant located in the Arctic region of the Russian Federation and to choose an effective option for the project implementation. It is shown that the design and implementation of projects for the construction of thermal power plants under conditions of instability of permafrost is characterized by the complexity of planning, large costs and a large number of operations. The practical significance of the work is determined by the possibility to apply the presented procedure for managing the design and construction process of a thermal power plant under conditions of permafrost instability when it is necessary to construct new thermal power plants in the Arctic region of the Russian Federation.